Epigenomic and metabolic responses of hypothalamic POMC neurons to gestational nicotine exposure in adult offspring. Issue 1 (December 2016) - Silva, Jose; Lambert, Guerline; van Booven, Derek; Wahlestedt, Claes
Abstract Background Epidemiological and animal studies have reported that prenatal nicotine exposure (PNE) leads to obesity and type-2 diabetes in offspring. Central leptin-melanocortin signaling via hypothalamic arcuate proopiomelanocortin (POMC) neurons is crucial for the regulation of energy and glucose balance. Furthermore, hypothalamic POMC neurons were recently found to mediate the anorectic effects of nicotine through activation of acetylcholine receptors. Here, we hypothesized that PNE impairs leptin-melanocortinergic regulation of energy balance in first-generation offspring by altering expression of long non-coding RNAs (lncRNAs) putatively regulating development and/or function of hypothalamic POMC neurons. Methods C57BL/6J females were exposed ad libitum to nicotine through drinking water and crossed with C57BL/6J males. Nicotine exposure was sustained during pregnancy and discontinued at parturition. Offspring development was monitored from birth into adulthood. From the age of 8 weeks, central leptin-melanocortin signaling, diabetes, and obesity susceptibility were assessed in male offspring fed a low-fat or high-fat diet for 16 weeks. Nicotine-exposed and non-exposed C57BL/6J females were also crossed with C57BL/6J males expressing the enhanced green fluorescent protein specifically in POMC neurons. Transgenic male offspring were subjected to laser microdissections and RNA sequencing (RNA-seq) analysis of POMC neurons for determination of nicotine-induced gene expression changes and regulatory lncRNA/protein-coding gene interactions. Results Contrary to expectation based on previous studies, PNE did not impair but rather enhanced leptin-melanocortinergic regulation of energy and glucose balance via POMC neurons in offspring. RNA-seq of laser microdissected POMC neurons revealed only one consistent change, upregulation ofGm15851, a lncRNA of yet unidentified function, in nicotine-exposed offspring. RNA-seq further suggested 82cis -regulatory lncRNA/protein-coding gene interactions, 19 of which involved coding genes regulating neural development and/or function, and revealed expression of several previously unidentified metabolic, neuroendocrine, and neurodevelopment pathways in POMC neurons. Conclusions PNE does not result in obesity and type 2 diabetes but instead enhances leptin-melanocortinergic feeding and body weight regulation via POMC neurons in adult offspring. PNE leads to selective upregulation ofGm15851, a lncRNA, in adult offspring POMC neurons. POMC neurons express several lncRNAs and pathways possibly regulating POMC neuronal development and/or function.